The duration and position of sitting associated with the occurrence of low back pain in e-sports players - Ida Bagus Adi Wahyu Wiraduta Kemenuh; I Dewa Gede Alit Kamayoga; Nila Wahyuni; Govinda Vittala (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: In the modern era, the rapid development of technology has affected many aspects of life, including the increasing popularity of online gaming among teenagers and adults. As a form of professional video game competition, e-sports has been recognized globally and nationally. However, prolonged gaming activities in a static sitting position often lead to health problems, one of which is low back pain (LBP). This study aimed to assess the association between sitting position and sitting duration with the incidence of LBP in e-sports players. Methods: This study used an observational design with a cross-sectional approach. The study sample totaled 68 e-sports players in East Denpasar who were selected through a purposive sampling method. The inclusion criteria were 20-30 years old and had an average body mass index (BMI), while the exclusion criteria had injuries to the wrist or spine. Data were collected using the rapid whole body assessment (REBA) worksheet questionnaire to assess the sitting position and the modified oswestry low back pain disability questionnaire (M-ODI) to determine the incidence of LBP. Data were analyzed using the Spearman correlation test. Results: The results showed that most of the sample had a moderate risk of sitting position (95.7%) and sitting more than 4 hours per day (67.6%). Correlation analysis showed a significant relationship between sitting position and LBP incidence (r = 0.371; p < 0.05) and between sitting duration and LBP incidence (r = 0.585; p < 0.05). The positive correlation value indicates that the worse the sitting position and the longer the sitting duration, the higher the risk of LBP. Conclusion: This study concludes that sitting position and duration are significantly associated with the incidence of LBP in e-sports players. This study is expected to educate e-sports players on the importance of ergonomic sitting positions and limiting sitting duration to reduce the risk of LBP.